2019
DOI: 10.1172/jci.insight.128664
|View full text |Cite
|
Sign up to set email alerts
|

Heat-killed Mycobacterium tuberculosis prime-boost vaccination induces myeloid-derived suppressor cells with spleen dendritic cell–killing capability

Abstract: models of live Mycobacterium tuberculosis infection (11). Whether vaccines containing killed M. tuberculosis would also induce MDSCs remains unclear.Among the carrier substances for antitumor or antipathogen vaccines, incomplete Freund's adjuvant (IFA), used under the name Montanide ISA-51 VG, is a suitable and widely distributed mineral oil-based adjuvant for human clinical studies with good antigen responses but also some adverse effects (12,13). Another preparation, CFA, was developed in 1942 and since then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 54 publications
0
31
0
Order By: Relevance
“…The presence of M-MDSCs in high number was observed in the patients with LL and T2R patients with BCG vaccination scar. Some studies have described that the BCG vaccination or inoculation with M. tuberculosis antigens induce the MDSC migration [35,36]. This data and other genetic polymorphisms might make those patients more susceptible to developing the worst symptoms of leprosy.…”
Section: Discussionmentioning
confidence: 87%
“…The presence of M-MDSCs in high number was observed in the patients with LL and T2R patients with BCG vaccination scar. Some studies have described that the BCG vaccination or inoculation with M. tuberculosis antigens induce the MDSC migration [35,36]. This data and other genetic polymorphisms might make those patients more susceptible to developing the worst symptoms of leprosy.…”
Section: Discussionmentioning
confidence: 87%
“…However, no differences were found for the cell subset frequencies ( Figure 1D ). LPS/IFN-γ represents a strong inducer of MDSC activation (A-MDSCs) leading to the release of NO as a major suppression mechanism for T cells ( 5 ) and dendritic cells ( 9 ). A-MDSCs showed no difference in their VLA-1 expression as compared to R-MDSCs.…”
Section: Resultsmentioning
confidence: 99%
“…In mycobacteria-vaccinated mice MDSC accumulation occurred preferentially in the red pulp and bridging channels. An inflammatory challenge directed them into the white pulp and activated them to induce dendritic cells (DC) killing but left the white pulp T cells unaffected ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Deficiency in arginine-1 inhibits T cell proliferation by impairing CD3 ζ-chain synthesis, which as a consequence prevents upregulation of the expression of cell cycle regulators cyclin D3 and cyclin-dependent kinase 4 (54). NO suppresses T cell function by inducing T cell apoptosis or blocking JAK3 and STAT5 function in T cells (53) or by killing DCs (5). We observed that Cav1 −/− MDSCs displayed defects in the NO production and T cell suppression.…”
Section: Discussionmentioning
confidence: 99%
“…We found that MDSCs were expanded in the blood of TB patients and decreased after successful chemotherapy (4), and that vaccinations using Mtb can accumulate MDSCs in the spleens of mice (5). In a murine model of TB infection, MDSCs phagocytosed Mtb and secreted IL-10, IL-6, and IL-1α (6).…”
Section: Introductionmentioning
confidence: 99%